BMP9 and BMP10: Two close vascular quiescence partners that stand out. Issue 1 (19th July 2021) - Desroches‐Castan, Agnès; Tillet, Emmanuelle; Bouvard, Claire; Bailly, Sabine
Abstract: Bone morphogenetic proteins (BMPs) are dimeric transforming growth factor ß (TGFß) family cytokines that were first described in bone and cartilage formation but have since been shown to be involved in many pleiotropic functions. In human, there are 15 BMP ligands, which initiate their cellular signaling by forming a complex with two copies of type I receptors and two copies of type II receptors, both of which are transmembrane receptors with an intracellular serine/threonine kinase domain. Within this receptor family, ALK1 (activin receptor‐like kinase 1), which is a type I receptor mainly expressed on endothelial cells, and BMPRII (BMP Receptor type II), a type II receptor also highly expressed on endothelial cells, have been directly linked to two rare vascular diseases: hereditary hemorrhagic telangiectasia (HHT), and pulmonary arterial hypertension (PAH), respectively. BMP9 (gene name GDF2 ) and BMP10, two close members of the BMP family, are the only known ligands for the ALK1 receptor. This specificity gives them a unique role in physiological and pathological angiogenesis and tissue homeostasis. The aim of this current review is to present an overview of what is known about BMP9 and BMP10 on vascular regulation with a particular emphasis on recent results and the many questions that remain unanswered regarding the roles and specificities between BMP9 and BMP10. Key Findings: BMP9 and BMP10 are two growth factors that bind to the endothelial receptor ALK1. BMP9 and BMP10 play key specific and redundant roles in vascular quiescence in autocrine, paracrine and endocrine manners. BMP9 and BMP10 pathways are involved in two rare vascular diseases: hereditary haemorrhagic telangiectasia (HHT), and pulmonary arterial hypertension (PAH).